Surgical Treatment of Coronary Heart Disease Against the Background of Coagulopathy of Unknown Etiology. Case Report - Rudenko, Mykola L.; Unitska, Olha M.; Cherpak, Anna Yu. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Coronary heart disease (CHD) is one of the most common cardiovascular diseases and one of the leading causes of death in the world. Diet is the first step in the prevention of CHD. Vegetarians have significantly lower risk of death from CHD, but also have changes in the hemostasis system due to a deficiency of blood clotting factors. Cardiosurgical intervention for patients with hemostatic disorders should be performed in specialized centers with the necessary support. Case description. A 73-year-old patient G. was hospitalized to the National Amosov Institute of Cardiovascular Surgery with angina pectoris, weakness and edema. From the past medical history it is known that the patient has been following a diet with complete exclusion of meat and dairy products for 20 years, rarely eats fish; in addition, he smoked for 20 years at a young age. After coronary angiography, the patient developed bleeding from the oral cavity of unknown origin, which resolved on its own. According to the examination, the patient was found to have a multivessel lesion of the coronary arteries, and cardiosurgical intervention was indicated: coronary bypass surgery. At a case conference with cardiovascular surgeons, anesthesiologist and cardiologist, a decision was made to perform salvage cardiac surgery. The predicted mortality risk was 7.0% by the EuroSCORE II. The early postoperative period was complicated by bleeding with subsequent revision of the pericardium to identify the source of bleeding. Coagulopathy of unknown origin was suspected. Replacement hemostatic therapy was started, which included massive blood transfusions. The pace and level of exudation significantly decreased, the operation was completed. After surgical interventions and hemotransfusions, thromboelastography was performed and plasma hypercoagulation was detected. The patient was discharged for continued cardiopulmonary rehabilitation, and outpatient treatment was prescribed. Conclusions. This case report describes successful treatment of multivessel coronary artery disease by bypass grafting in a vegetarian patient with a coagulation disorder. Studies of the effects of a vegetarian diet on the hemostatic system indicate that vegetarians may have lower concentrations of hemostatic factors and that thrombin time is also prolonged due to the nutritional guidance provided by this diet. In addition, timely detection of a deficiency of blood coagulation factors in the plasma of a patient with such history can facilitate the diagnosis of the hemostasis system.